“METRIKA”: Electronics Trainer Media for Supporting Learning in the Application of Ohm's Law and Kirchhoff's Law - Andrian Nur Sya'ban; Delsina Faiza; Thamrin; Ilmiyati Rahmy Jasril (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
The design of Ohm’s Law and Kirchoff’s Law trainers is an innovation aimed at improving the effectiveness process, particularly in the subjects of Ohm’s Law and Kirchoff’s Law. This trainer utilizes an AC-to-DC converter module and a DC-to-DC step-down module as the main power supply. The main structure of the trainer is divided into three key parts: the power supply, circuitry, and measurement tools. Ohm’s Law and Kirchoff’s Law are the focus in selecting the material, as they constitute the fundamental laws in electronics. During practical exercises, students often encounter challenges related to neatness, the structure of the materials, and practical tools. The trainer is expected to overcome these issues by providing a more structured and practical environment. By utilizing this trainer, it is expected that students can more easily comprehend and practically apply the concepts of Ohm’s Law and Kirchoff’s Law. Based on the test results, the trainer can provide measurement results that closely approximate accuracy with minimal differences from manual calculations. This indicates that the trainer will provide a consistent, practical experience in line with fundamental electronic principles. Moreover, the learning process can become more organized and efficient, improving the overall quality of learning in the basic electronic law.